Engineered three-dimensional rabbit oral epithelial–mesenchymal–muscular hybrid sheets - Yamane, Shigeki (Int J Oral Sci, 2016)
Regenerative muscles are required for swallowing and mastication, and are important for functional recovery from diseases involving oral muscular defects. Therefore, we generated three-layer hybrid sheets, similar to oral mucosal structures containing submucosal muscles, using rabbit oral mucosa epithelial, mesenchymal, and myoblastic progenitor cells, and examined the structural proteins. Each cell type was obtained from rabbit oral mucosa using enzymatic digestion. Isolated mesenchymal and myoblastic cells were multi-differentiated into osteoblasts, adipocytes, and chondrocytes or myotubes. Isolated epithelial cells were cultured on collagen gels containing isolated mesenchymal cells for 2 weeks, and these epithelial–mesenchymal cell sheets were laminated onto myoblastic cell sheets. The engineered hybrid sheets were multi-stratified in the epithelial and myoblastic layers in a time-dependent manner, expressing intermediate cytoskeletal filament proteins of epithelium and muscle. Hybrid sheets also expressed extracellular matrix basement membrane proteins. Immature cell markers for epithelial and myoblastic cells were observed continuously in hybrid sheet cultures. We established engineered three-dimensional rabbit oral mucosa hybrid sheets containing each immature cell type in vitro.